2016
DOI: 10.3174/ajnr.a4811
|View full text |Cite
|
Sign up to set email alerts
|

WEB Treatment of Ruptured Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE:The Woven EndoBridge (WEB) device was recently introduced for intrasaccular treatment of wide-neck aneurysms without the need for adjunctive support. We present our first experience in using the WEB for small ruptured aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
(21 reference statements)
0
24
0
1
Order By: Relevance
“…Since the first clinical experience reported in 2012,8 the WEB dual layer (WEB-DL, figure 1A) has been replaced by a single layer device (WEB-SL, figure 1B), and a second device with a spherical shape has also been developed (WEB-SLS, figure 1C) 9. Early series have reported good clinical and anatomical outcomes in unruptured8 10–14 and ruptured IA 9 15 16. However, few data are available on mid term12 17 18 and long term follow-up,19 which raise questions about long term stability of neck remnants related to potential device compression 17…”
Section: Introductionmentioning
confidence: 99%
“…Since the first clinical experience reported in 2012,8 the WEB dual layer (WEB-DL, figure 1A) has been replaced by a single layer device (WEB-SL, figure 1B), and a second device with a spherical shape has also been developed (WEB-SLS, figure 1C) 9. Early series have reported good clinical and anatomical outcomes in unruptured8 10–14 and ruptured IA 9 15 16. However, few data are available on mid term12 17 18 and long term follow-up,19 which raise questions about long term stability of neck remnants related to potential device compression 17…”
Section: Introductionmentioning
confidence: 99%
“…Introduced in 2010 in Europe, the Woven Endo-Bridge (WEB; Sequent Medical, Aliso Viejo, California) is the only intrasaccular device that has been extensively evaluated in the literature with several single-and multicenter, retrospective, and prospective series. [9][10][11][12][13][14][15][16][17][18][19][20][21] Good Clinical Practice studies, including the WEB Clinical Assessment of IntraSaccular Aneurysm Therapy (WEBCAST) and the French Observatory studies, have shown a high level of safety with the device. [15][16][17][18] Efficacy has to be further evaluated, but 1-year anatomic results in both the WEB-CAST and French Observatory studies are encouraging.…”
mentioning
confidence: 99%
“…Most thromboembolic complications were due to catheterization and not to the WEB. 1,[3][4][5]7 Clinical results in our practice have improved since the WEB replaced stent-assisted coiling, especially in ruptured aneurysms. 2,4 The simple periprocedural anticoagulation protocol without antiplatelet medication is a great advantage.…”
Section: Clinical and Imaging Results And Implications For Practicementioning
confidence: 99%
“…To further master the technique of the WEB, we gradually expanded the indication to all aneurysms suitable for the WEB; in general, small aneurysms from 3 to 10 mm, regardless of neck size or location. [3][4][5] The Figure is a graphic display of the use of the WEB, coils, additional supporting devices, and flow diverters for endovascu-lar treatment of intracranial aneurysms in our practice during 2013-2017.…”
Section: How Did We Start?mentioning
confidence: 99%